Structural Drivers, Barriers, and Institutional Actors in an Indonesian Sheep Export Supply Chain: A Retrospective ISM Case Study - Afif Fajar Mey Wulandari; Dhanang Eka Putra (CV. SPDFHarmony, 2026)
Background: Export-oriented livestock supply chains require coordination among animal procurement, farmer-based fattening, finance, regulatory compliance, and export intermediation. This study examined the structural relationships among needs, barriers, and institutional actors in the sheep export supply chain of CV Gumukmas Multi Farm in Jember, Indonesia. Methods: A retrospective descriptive single-case study used archived evidence collected during August–October 2020 and March–May 2021. Data sources included observation, semi-structured interviews, company records, expert discussions, and structured Interpretive Structural Modeling questionnaires. Three purposively selected domain experts represented company management, ruminant-livestock academia, and the livestock authority. The ISM assessment comprehensively covered seven supply-chain needs, nine barriers, and ten institutional actors. Results: The historical chain connected livestock traders, the focal enterprise, 87 partner farmers, and PT Inkopmar Cahaya Buana as the export intermediary. Capital availability emerged as the principal independent driver among supply-chain needs. Lengthy export licensing was the most fundamental barrier, whereas capital limitation, sheep shortage, and limited transparency were also upstream constraints. Financial institutions were the strongest independent institutional actor; suppliers, exporters, livestock authorities, government agencies, and investors occupied linkage positions. Conclusion: The findings support a sequenced improvement pathway that begins with workable financing and regulatory coordination, followed by linked investments in internal breeding, feed technology, farmer capability, and partnership transparency. The study contributes a historically situated ISM interpretation of live-animal export coordination. Because the case relied on one enterprise, three experts, and incomplete archived numerical matrices, the hierarchy should inform case-specific prioritisation and be updated through a contemporary, fully auditable multi-stakeholder study.